2021
DOI: 10.1007/s11136-021-02848-8
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in elderly, multimorbid individuals with and without depression and/or mild cognitive impairment using a telemonitoring application

Abstract: Purpose Multimorbidity leads to decreasing health-related quality of life (HRQoL). Telemedicine may help to improve HRQoL. The present study was conducted to show (I) differences in HRQoL and changes in HRQoL over time in elderly, multimorbid individuals with and without depression and/or mild cognitive impairment (MCI) using a telemonitoring application (TMA) and (II) associations between engagement with measurements by study participants using a TMA and changes in their HRQoL. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…However, most of them were conducted in high-income countries and the tools employed to measure QoL among people living with multimorbidity have not been consistent [40]. Some studies in high-income countries used Euro QoL (EQ-5D-5l) [41,42], while others used either WHOQOL brief [40] or SF-36 [40,43] or SF-12 tools [40,[44][45][46]. Although the use of all of these tools has been widespread, the short form (SF-12) version is an efficient algorism to reproduce SF-36 tool to measure health related quality of life [47].…”
Section: Introductionmentioning
confidence: 99%
“…However, most of them were conducted in high-income countries and the tools employed to measure QoL among people living with multimorbidity have not been consistent [40]. Some studies in high-income countries used Euro QoL (EQ-5D-5l) [41,42], while others used either WHOQOL brief [40] or SF-36 [40,43] or SF-12 tools [40,[44][45][46]. Although the use of all of these tools has been widespread, the short form (SF-12) version is an efficient algorism to reproduce SF-36 tool to measure health related quality of life [47].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of depression, although it is strongly correlated with the psychological domains of HRQoL, there is evidence that it also impacts the physical domains [34‐36]. Lang et al showed similar results in older people living with HIV, correlating depression and mild cognitive impairment with poor PCS and MCS [37]. Unfortunately, our results did not show that higher levels of depressive symptoms correlated with a worse PCS or that decreased cognitive function correlated with MCS in people living with HIV aged ≥60 years.…”
Section: Discussionmentioning
confidence: 99%
“…Although younger populations could benefit from socioeconomic and clinical interventions, our results showed that the HRQoL of older people living with HIV only correlated with depression, social role, and cognitive function. Therefore, it might be more important to offer social and mental health support to these people as these are the main factors related to their overall wellbeing [37].…”
Section: Discussionmentioning
confidence: 99%
“…Canadian Journal on Aging / La Revue canadienne du vieillissement QoL represents the subjective and perceived health status of an individual, and encompasses multiple items related to one's physical, psychological, and social well-being (Mortada, Salem, Elseifi, & Khalil, 2018). It is frequently measured using deficit-oriented measures, such as functional decline (Edvardsson et al, 2019), and it is monitored to determine and address the respective needs of individuals and to improve decision-making in health care settings (Lang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that more than 75 per cent of older adults live with one or more chronic diseases (Canadian Medical Association, 2016). Frailty is highly prevalent among older adults admitted to LTC, and quality of life (QoL) has been recognized as an important indicator for health outcomes of LTC residents (Kehyayan et al, 2015; Lang, Roessler, Schmitt, Bergmann, & Holthoff-Detto, 2021).…”
Section: Introductionmentioning
confidence: 99%